2018
DOI: 10.1186/s12887-018-0991-4
|View full text |Cite
|
Sign up to set email alerts
|

The presentation of a short adapted questionnaire to measure asthma knowledge of parents

Abstract: BackgroundThe aim of this study is to establish asthma knowledge of parents of children (0–18 years) with asthma at the outpatient clinic.MethodsA translated and adapted a 21 item Likert type 5 point scale questionnaire (Cronbach’s α-coefficient 0.73) was completed by 291 parents of children with asthma. Total asthma knowledge scores were associated with demographic and psychosocial variables.ResultsFactor analysis resulted in a new reduced 10 item questionnaire (Cronbach’s α-coefficient 0.72). Higher educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
1
7
0
2
Order By: Relevance
“…Higher education levels were associated with membership in the “good knowledge” class, consistently with several previous studies [ 2 , 7 , 8 , 14 ]. Indeed, mothers with higher education may be more likely to have prior knowledge and more inclined to gather and absorb new information [ 8 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Higher education levels were associated with membership in the “good knowledge” class, consistently with several previous studies [ 2 , 7 , 8 , 14 ]. Indeed, mothers with higher education may be more likely to have prior knowledge and more inclined to gather and absorb new information [ 8 ].…”
Section: Discussionsupporting
confidence: 90%
“…Current evidence shows that the parental level of asthma-related knowledge may influence asthma management practices [ 2 ] and affect children’s disease control [ 3 , 4 , 5 , 6 ]. Much of the existing literature studying the impact of parental knowledge on childhood asthma outcomes focuses on mothers as the primary caregivers [ 5 , 7 , 8 , 9 , 10 , 11 ], suggesting that asthma in children is majorly managed by mothers. Therefore, assessing mothers’ knowledge and practices is essential for improving the management of childhood asthma.…”
Section: Introductionmentioning
confidence: 99%
“…2 Asthma is prevalent among underprivileged, minority, and urban children, who also endure a disproportionate burden of preventable asthma-related morbidity including emergency department (ED) visits, hospitalization, and missed days of school. 3 A multistate survey to identify racial disparities in children with asthma showed that 39% of Black children had asthma-related ED visits and hospitalizations compared with 18% of White children. 4 …”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that asthma exacerbations are preventable when patients and caregivers receive formal education for asthma self-management. 3 , 9 Empowering children and caregivers with the required knowledge and self-management skills is necessary to achieve proper asthma control. 10 Despite this evidence, parents of children with asthma continue to have various misconceptions regarding asthma management.…”
Section: Introductionmentioning
confidence: 99%
“…A short adapted 20 item questionnaire, developed based on study by Franken et al . [5] was self administered to 120 students before the lecture to assess baseline knowledge on epidemiology, causation, prevention and management of asthma. Same was administered again to assess post lecture change.…”
mentioning
confidence: 99%